Does temperament make children differently susceptible to their home physical food environment? A cross-sectional DAGIS study on 3–6 year old Finnish children's food consumption. (1st June 2021) - Pajulahti, Riikka; Salmela-Aro, Katariina; Lehto, Reetta; Vepsäläinen, Henna; Lehto, Elviira; Nissinen, Kaija; Skaffari, Essi; Sääksjärvi, Katri; Roos, Eva; Sajaniemi, Nina; Erkkola, Maijaliisa; Ray, Carola
Abstract: Consistently linked with children's food consumption are food availability and accessibility. However, less is known about potential individual differences among young children in their susceptibility to home food environments. The purpose of the study was to examine whether the association between home food availability and accessibility of sugar-rich foods and drinks (SFD) or fruits and vegetables (FV) and children's consumption of these foods differ according to their temperament. The study used two cross-sectional datasets collected as part of the Increased Health and Wellbeing in Preschools (DAGIS) study: 1) a cross-sectional data of 864 children aged 3–6 years old collected between fall 2015 and spring 2016, and 2) an intervention baseline data of 802 children aged 3–6 collected in fall 2017. Parents reported their children's temperament, consumption of FV and SFD, and home availability and accessibility of SFD and FV. Examination of whether associations between home availability and accessibility of FV and their consumption differ according to children's temperament involved using linear regression models. Similar models were used to examine association between home availability and accessibility of SFD and their consumption, and the moderating role of temperament. The association between home accessibility of SFD and their consumption frequency was dependent on the level of children's negative affectivity. More frequent consumption of SFD was observed with higher home accessibility of SFD. The association was stronger in children with higher scores in negative affectivity. No other interactions were found. Children with higher negative affectivity are possibly more vulnerable to food cues in the home environment than children with lower negative affectivity. Consideration of children's individual characteristics is necessary in supporting their healthy eating.